Comparison of Intramuscular Versus Rectal Diclofenac Sodium in Post Caesarean Pain Relief - Altaf, Beenish; Kashif, Sanum; Sial, Shagufta Saeed; Noreen, Humera; Pervaiz, Erum; Awan, Shazia Mahmood (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the mean post-operative pain after intramuscular versus rectal Diclofenac Sodium in post-caesarean patients.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Obstetrics & Gynaecology, Benazir Bhutto Hospital, Rawalpindi Pakistan, from May to Nov 2017.Methodology: A total of 60 women, aged 18-45years, undergoing elective caesarean section were selected. Patients in Group-A were given, Diclofenac 75mg intramuscularly in the gluteal area every 8 hours, while patients in Group-B received a Diclofenac Sodium suppository every 8 hours post-operatively. All patients were followed for pain post-operatively, and final post-caesarean pain was noted at 24 hours post-operatively using a visual analogue scale.Results: The mean age of patients in the Group-A was 29.27±4.68 years, and in Group-B was 30.57±4.80years. The range of gestational age in the study was from 37 to 41 weeks, with an average age of 39.07±1.26 weeks. Mean post-operative pain in Group-A (Intramuscular Diclofenac Sodium-Group) was 1.13±0.43 minutes, whereas in Group-B (Rectal Diclofenac SodiumGroup), was 2.16±0.83 (p-value = 0.001).Conclusion: Mean post-operative pain after using intramuscular Diclofenac sodium is less than Diclofenac Sodium administered rectally in post-operative patients in caesarean sections.